A 3D model for architectural analysis, using aerial photogrammetry, for the digital documentation of the convent of Santa Maria da Ínsua, on the northern border between Portugal and Spain. - Volzone, R.; Becherini, P.; Cottini, Anastasia (D-SITE, Drones - Systems of Information on culTural hEritage, 2022)
The convent of Santa Maria da Ínsua, northern of Portugal, was founded in 1392 by the Observant Franciscans. The space has been studied mostly by Historians but an in-depth analysis of its physical evidences is missing. This paper seeks to fill in this gap, in order to contribute to the diffusion of this religious heritage site. This study is even more relevant in this historical moment because it is conducted exactly before the building rehabilitation. Digital photogrammetric surveys through UAVs provide a quick method to obtain a 3D textured mesh model for further studies, online visualization, preservation and sharing.